2008
DOI: 10.1177/1098611107309564
|View full text |Cite
|
Sign up to set email alerts
|

Police Officers and Their Alcohol Consumption

Abstract: Alcohol use by police officers in the United States is theorized to be double that of the general population, with 20% of those abusing alcohol. However, no known alcohol consumption study has been conducted within the United States. This study hoped to fill that void. Full time Mississippi officers from municipal, county, and state departments totaling 1,328, were asked to complete a 27-item questionnaire containing the World Health Organization's Alcohol Use Disorders Identification Test instrument to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
(19 reference statements)
4
22
0
Order By: Relevance
“…While the current study has found a number of differences in the nature of crimes committed by policemen and policewomen, both male and female officers face similar experiences and stressors on the job. The finding is consistent with others indicating few or no differences between drinking behavior of male and female officers (Lindsay, 2008;Mandell et al, 1992;Stinson et al, 1992). Alcohol usage is a commonly recurring factor for off duty arrests of officers and may indicate both groups are susceptible to negative consequences of the stressful profession, although there is little research addressing potential alcohol-related spillover effects of police work into officers' personal lives (Violanti et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the current study has found a number of differences in the nature of crimes committed by policemen and policewomen, both male and female officers face similar experiences and stressors on the job. The finding is consistent with others indicating few or no differences between drinking behavior of male and female officers (Lindsay, 2008;Mandell et al, 1992;Stinson et al, 1992). Alcohol usage is a commonly recurring factor for off duty arrests of officers and may indicate both groups are susceptible to negative consequences of the stressful profession, although there is little research addressing potential alcohol-related spillover effects of police work into officers' personal lives (Violanti et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, scholars have found patterns of alcohol use are similar between male and female officers (Ballenger et al, 2011). While some have found policewomen are more likely to engage in binge drinking compared to male counterparts (Ballenger et al, 2011;Davey, Obst, & Sheehan, 2000), others found few or no differences (Lindsay, 2008;Mandell, Eaton, Anthony, & Garrison, 1992;Stinson, DeBakey, & Steffens, 1992). The following section reviews the limited knowledge we have on police crime by gender.…”
Section: The Nature Of Police Crimementioning
confidence: 94%
“…Heavy alcohol drinking, which is associated with increased caloric intake, has been linked to an increased BMI [39,40]. Previous research [41], however, found that among police officers in Mississippi, those with the greatest risk of drinking problems were young, white, and unmarried day-shift officers. Also, the prevalence of drinking among Mississippi officers was similar to that of the United States general population [41].…”
Section: Discussionmentioning
confidence: 99%
“…Having analyzed the media education theories developed by media educators from different countries Irina Fateeva concluded that "to derive a media education theory from communication theories is not only unreasonable but also destructive since that initially causes conceptual disunity of teachers and their pupils intensified by moral and ethical problems: after failing to reach a consensus in the dispute the teachers are apt to impose their arguable views on the audience" [Fateeva, 2007, p. [25][26].…”
Section: Alcohol Abuse By Policementioning
confidence: 99%